[STIX]x1D6F7-CARLESON MEASURES AND MULTIPLIERS BETWEEN BERGMAN–ORLICZ SPACES OF THE UNIT BALL OF C^n. (22nd March 2017) - SEHBA, BENOÎT F.
Abstract : We define the notion of [STIX]x1D6F7 -Carleson measures, where [STIX]x1D6F7 is either a concave growth function or a convex growth function, and provide an equivalent definition. We then characterize [STIX]x1D6F7 -Carleson measures for Bergman–Orlicz spaces and use them to characterize multipliers between Bergman–Orlicz spaces.